Differential lysine‐mediated allosteric regulation of plant dihydrodipicolinate synthase isoforms. (2nd March 2021) - Hall, Cody J.; Lee, Mihwa; Boarder, Matthew P.; Mangion, Alexandra M.; Gendall, Anthony R.; Panjikar, Santosh; Perugini, Matthew A.; Soares da Costa, Tatiana P.
Abstract : Lysine biosynthesis in plants occurs via the diaminopimelate pathway. The first committed and rate‐limiting step of this pathway is catalysed by dihydrodipicolinate synthase (DHDPS), which is allosterically regulated by the end product, l ‐lysine (lysine). Given that lysine is a common nutritionally limiting amino acid in cereal crops, there has been much interest in probing the regulation of DHDPS. Interestingly, knockouts in Arabidopsis thaliana of each isoform (AtDHDPS1 and AtDHDPS2) result in different phenotypes, despite the enzymes sharing > 85% protein sequence identity. Accordingly, in this study, we compared the catalytic activity, lysine‐mediated inhibition and structures of both A. thaliana DHDPS isoforms. We found that although the recombinantly produced enzymes have similar kinetic properties, AtDHDPS1 is 10‐fold more sensitive to lysine. We subsequently used X‐ray crystallography to probe for structural differences between the apo‐ and lysine‐bound isoforms that could account for the differential allosteric inhibition. Despite no significant changes in the overall structures of the active or allosteric sites, we noted differences in the rotamer conformation of a key allosteric site residue (Trp116) and proposed that this could result in differences in lysine dissociation. Microscale thermophoresis studies supported our hypothesis, with AtDHDPS1 having a ~ 6‐fold tighter lysine dissociation constant compared to AtDHDPS2, which agrees with the lower half minimal inhibitory concentration for lysine observed. Thus, we highlight that subtle differences in protein structures, which could not have been predicted from the primary sequences, can have profound effects on the allostery of a key enzyme involved in lysine biosynthesis in plants. Databases: Structures described are available in the Protein Data Bank under the accession numbers 6VVH and 6VVI . Abstract : Understanding the regulation of amino acid biosynthesis in plants is essential to producing crops with improved nutrition. In this study, we show that the two dihydrodipicolinate synthase isoforms from Arabidopsis thaliana, involved in lysine biosynthesis, are differentially regulated by the end‐product, lysine. We propose that this is due to an allosteric site tryptophan residue, which adopts different conformations in each isoform, thus playing a key role in lysine dissociation.